The NTD Supply Chain Forum—Strengthening the backbone of NTD programs - Souza, Ashley A.; Holloway, Cassandra; Williams, Tijana (PLOS Neglected Tropical Diseases, 2020)
Author summary Neglected tropical diseases (NTDs) are a diverse group of diseases that disproportionately affect the world’s disadvantaged populations. Five of the diseases—lymphatic filariasis (LF), schistosomiasis (SCH), soil-transmitted helminthiasis (STH), onchocerciasis (ONC), and trachoma (TRA)—are collectively known as the preventive chemotherapy NTDs (PC-NTDs) because the intervention strategy for each is based on delivery of preventive treatment to the entire eligible, at-risk population via mass drug administration (MDA). The global programs targeting these diseases are made possible through the generous donation of drugs from 6 pharmaceutical companies: Eisai; Johnson & Johnson (J&J); GlaxoSmithKline (GSK); Merck & Co., Inc., Kenilworth, New Jersey, United States of America (MSD); Merck KgaA; and Pfizer. Today, the scale of the PC-NTD drug donation programs is staggering. Nearly 15 billion tablets have been manufactured, packaged, shipped, and distributed. The supply chains established to support such massive operations are enormously complex. The Coronavirus Disease 2019 (COVID-19) pandemic has thrust the importance of strong supply chains into global focus like never before. It is therefore an opportune moment to recognize the supply chains that form the backbone of global PC-NTD programs and the unique public–private partnership that was formed to strengthen them.